Study of the Genetic Structure of Iranian Native dogs Using Mitochondrial DNA information - Mahboubeh Alizadeh (مجله بیوتکنولوژی کشاورزی, 2014)
in comparison with the exotic breeds. To follow this, blood samples of 93 dogs were obtained from diverse areas of Iran and, in addition, 655 sequences of canine D-loop region obtained from GenBank. Total DNA of the samples were extracted by salting out procedure and applied as template for amplification and sequencing of the D-loop region of mtDNA. Sequence analysis of the 582-bp D-loop region of mtDNA in all samples defined a total of 25 haplotypes. The total nucleotide diversity was 0.01354± 0.00704 for Iranian native dogs. Analysis of molecular variance (AMOVA) showed significant percent for the variance between the studied populations (ΦST=0.029, P=0.0000). Fixation index values using F-Statistics method ranged from -0.02671 to 0.3748. Analysis of molecular variance displayed significant difference between some of these populations. The variation was especially observed between Tazi and Sarabi, Bakhtiari, Alborz native and Western regions populations or between Sarabi population with Kurdi, Sangsari, Alborz native and Western regions populations. Bakhtiari population showed a significant difference (P > 0.05) with Alborz native and Western regions populations, and finally European breeds exhibited a difference with South West Asia breeds. In addition Tazi, Sangsari and Western regions populations displayed significant difference with European breeds and South West Asia breeds (P > 0.05). Overall, the results of this study showed an acceptable genetic variation and genetic similarity in some Iranian dog populations.